Estudio de la normatividad de los precios de transferencia en la empresa Camposol S.A. del ejercicio fiscal 2010. - Marquina Rodriguez, Maribel (2012)
This research aims to analyze the application of regulations relating to transfer pricing in the company Camposol S.A. in fiscal year 2010, for transactions between related parties, according to the provisions of article 32-A of the Income Tax DS No. 179-2004-EF. The problem statement is: how to apply the regulations relating to transfer pricing in the company Camposol S.A. in fiscal 2010 and the hypothesis is proposed: the regulations relating to transfer pricing is applied doctrine and reasonable in the company Camposol S.A. in fiscal 2010. It was used as a contrasting design: experimental investigation type - Transectional or Transversal Descriptive. Note that this is a thesis motivated in learning and studying the national policy framework for transfer pricing. The results obtained in this investigation demonstrate that the company Camposol S.A. in fiscal year 2010, is immersed within the scope of the regulatory framework of transfer pricing. It can be concluded that the transactions entered into by the company under study with its related companies for tax purposes for that year, comply with the principle of arm's length or length. It was found that the most appropriate valuation method for the analysis of transactions subject to the application of the method of transfer is comparable uncontrolled price. Finally, we determined the formal obligations to which it is bound Camposol S.A. in fiscal year 2010 for tax purposes, such as: Presentation of the Annual Affidavit and the development of the Technical Study.